منهج تعليم اللغة العربية بالمدرسة الثانوية - Mochamad Hasyim (Universitas Yudharta Pasuruan, 2019)
There is no doubt that high school is gaining importance from its role and responsibilities in guiding teachers at this stage. It aims to help them adapt their behavior to the activities of the community and to create a social climate that promotes their individual and social well-being. The stage is considered to be a serious step forward in education in the Ardennes and in other countries. The seriousness of this stage comes from the process of comprehensive preparation of students, and the development of aspects of their personality, which integrates the psychological, spiritual, social and mental, and show the individual's readiness and abilities and tendencies in a clear manner of behavior and behavior. The multidimensional syllabus is used to teach Arabic in this school, which is based on four study plans, or courses: language course, cultural course, communication course, and general curriculum for language instruction. The Arabic language in this school is generally aimed at having three basic competencies: language proficiency, communicative competence and cultural competence.